Verification of the Radio Wave Absorption Effect in the Millimeter Wave Band of SWCNTs and Conventional Carbon-Based Materials - Seiki Chiba; Mikio Waki (Applied Sciences, 2021)
Using a sample coated with three types of carbon-based paints, namely single-wall carbon nanotube (SWCNTs), carbon black, and graphite, the amount of radio wave absorption for each was measured. SWCNTs proved to have the superior radio wave absorption effect in the millimeter band. Considering the change in the amount of radio wave absorption depending on the coating amount, three different coating thicknesses were prepared for each test material. The measurement frequency was set to two frequency bands of 28 GHz and 75 GHz, and the measurement method was carried out based on Japanese Industrial Standard (JIS) R1679 “Radio wave absorption characteristic measurement method in the millimeter wave band of the radio wave absorber.” As for the amount of radio wave absorption in the 28 GHz band, a maximum amount of radio wave absorption of about 6 dB was obtained when 35 m of CNT spray paint was applied. It was confirmed that the carbon black paint came to about 60% that of the SWCNT, and the graphite paint did not obtain much radio wave absorption even when the coating thickness was changed. Furthermore, even in the 75 GHz band, the radio wave absorption was about 7 dB when 16 μm of CNT spray paint was applied, showing the maximum value. Within these experimental results, the CNT spray paint has a higher amount of radio wave absorption in the millimeter wave band than paints using general carbon materials. Its effectiveness could be confirmed even with a very thin coating thickness of 35 μm or less. It was also confirmed that even with the same paint, the radio wave absorption effect changes depending on the difference in coating thickness and the condition of the coated surface.